Impact Of Work Family Conflict, Workload And Transformational Leadership On Student Burnout, University Of Mercu Buana Jakarta - Lisna Saragih; Djamarel Hermanto (Universitas Mercu Buana, 2023)
This study aims to determine and analyze the effect of work-family conflict, workload and transformational leadership on student burnout at Mercu Buana University Jakarta. The background of the research is that due to the Covid-19 pandemic, many people have to be patient to stay at home and work from home or Work from Home (WFH), the extended large-scale social restriction (PSBB) policy and the homecoming ban have resulted in companies extending WFH for their employees. In this study, the authors took 33,496 students from Mercu Buana University Jakarta and the number of samples to be taken using slovin calculations was 100 respondents. Data collection techniques in this study by conducting a survey directly on the object of research, namely the University of Mercu Buana Jakarta. The data analysis method used in this research is the Component or Variance Based Structural Equation Model. The data processing uses the Partial Least Square (Smart-PLS) version 3.0 PLS program. PLS (Partial Least Square) is an alternative model of covariance-based SEM. PLS can be used to confirm the theory; besides that, it can be used to explain whether or not there is a relationship between latent variables. The desired results develop concepts and models that are more integrated and can find unequivocal and consistent results and contradictions. This study found that work-family conflict and workload had a positive and significant effect on burnout. Meanwhile, transformational leadership was found to have a negative and significant impact on burnout. The results of this study can contribute to practical and academic fields.